Daisy Miller - James, Henry (London : Chancellor Press, 2001)
The young Daisy Miller, an American on holiday with her mother on the shores of Switzerland$1 (Bs Lac Leman, is one of James$1 (Bs most vivid and tragic characters. Daisy$1 (Bs friendship with an American gentleman, Mr. Winterbourne, and her subsequent infatuation with a passionate but impoverished Italian bring to life the great Jamesian themes of Americans abroad, innocence versus experience, and the grip of fate. As Elizabeth Hardwick writes in her Introduction, Daisy Miller (3z(Blives on, a figure out of literature who has entered history as a name, a vision.(3ys
Keywords: Manners and customs; England -- Social life and customs -- 19th century -- Fiction; United States -- Social life and customs -- 19th century -- Fiction